IMMU-63. IDH1 MUTATION REGULATE MYELOID CELLS PLASTICITY MEDIATING ANTI-GLIOMA IMMUNOTHERAPY - Alghamri, Mahmoud (Neuro Oncol, 2018)
Molecular characterization studies have illustrated that mutation in isocitrate dehydrogenase (mIDH1) enzyme, which is present in most patients with low grade glioma (LGG) and secondary glioma is correlated with better prognosis and survival [1]. We hypothesize that mIDH1 impacts tumor immunity by altering the phenotype and function of tumor infiltrating immune cells. To examine the role of mIDH1 on the immune tumor microenvironment (TME), we generated LGG glioma models using sleeping beauty system [2]. Mice bearing mIDH1 tumors exhibited longer median survival (MS) compared to the tumors harboring wtIDH1 (MS=163 vs. MS=70-day post-injection). Transcriptome analyses showed a positive enrichment in immune-stimulatory related gene families in mIDH1 tumors vs. wtIDH1 tumors; consistent with Human RNA-seq analysis from TCGA analysis. Using co-culture experiments followed by the in vivo characterization of immune cells within the TME, we showed that mIDH1 have higher expansion of CD11b+ Gr-1+ myeloid cells compared to wtIDH1 tumors (%MDSC/CD45+: 67.0% vs. 45.06%; P<0.05). Interestingly, CD11b+ Gr-1+ myeloid cells (MDSCs) from mIDH1 tumor expressed lower levels of immunosuppressive markers such as PD-L1 and CD80 which are involved in T-cell checkpoint inhibition. Consistent with this, TME-derived CD11b+ Gr-1+ myeloid cells from mIDH1 tumors didn’t inhibit tumor antigen specific T-cells’ expansion. Further analysis indicated that mIDH1 MDSCs also express lower levels of maturation markers suggesting that MDSCs from mIDH1 are at earlier maturation/differentiation stage. Interestingly, MDSCs depletion did not improve efficacy of immunotherapy in mIDH1; whilst in wtIDH1 bearing animals, survival increased to 70% when MDSCs depletion was combined with immunotherapy. In conclusion, mIDH1 expression in glioma cells impact the myeloid cells’ compartment possibly by changing the cytokine’s repertoire secreted by the tumor cells. This leads to reprogramming of myeloid cells within the TME which exhibit a non-immunosuppressive phenotype. 1. Ceccarelli, M., et al., 2016 2. Koschmann, C, et al., 2016